(3YQhV CfOdSjs - (3GdNRQLj, CHh eMeO, VjGA GdOjf, YHO Gddg Hf eMeO, (B626 (3g`s ((3YKeGf Hf eMeOs)
(3ChdgG (B:s
(3bGdCHh YHO Gddg eMeO GdeYQha HCHj GdLjT GdCfUGQj GdCfOdSj CMeO Gddg hCJhcd YdjghHYO abO bUOJ aj gPG GdeNJUQ Cf CPcQ Ydd GdCYGQjV GdCQHY hGdKdGKjf hGdVQhH GdKdGKI hGdSJjfs
(3BNQgG (B:s
(3GdeJOGQc CUdg aGYdf KeGf eQGJ OGQc GdbOe JWaj ZQGeG hVC (B: (3EP OQjQ Gdghi HGdeYfi LeMs
(3aj Chdg fbhd ddEeGe GdTGaYj hfbhd aj GdMOjK hCOYjI HGddZI GdYQHjI hGdJQcjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 124s
(3eYLe GdeDdajf(B: 1 / 460s
(3cTa GdXfhf(B: 2 / 1135s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdYQhV hGdbhGajs